Transforming Accounting and Bookkeeping Through Artificial Intelligence Technologies - V Basil Hans (Journal of Advanced Research in Accounting and Finance Management, 2026)
Artificial intelligence (AI) is moving quickly and changing accounting and bookkeeping by automating mundane activities, making data more accurate, and allowing for real-time financial analysis. This article looks at how AI-powered tools are used in modern accounting, such as automated data entry, smart reconciliation, fraud detection, and predictive financial reporting. AI helps accountants focus on more important tasks like strategy planning, advisory services, and compliance management by cutting down on manual effort and mistakes made by people. The paper also talks about the problems that come with using AI, such as data security, ethical issues, following the rules, and the need to train accountants. The article says that AI doesn’t replace the professional judgement of accountants, but it does change the profession a lot, making accountants and bookkeepers key partners in making decisions based on data.